Use of Antibiotics in Upper Respiratory Tract Infections in Tertiary Care Teaching Hospital of Delhi - Zulqarnain, Md.; Singh, Sanjit; Prasad, Abhishek; Abdullah; Palit, Tanaya (Journal of Drug Delivery and Therapeutics, 2021)
The aim of this study was to evaluate the prescribing pattern of antibiotics in URTI patients attending the OPD and IPD of HAHC Hospital, a tertiary care teaching hospital of Jamia Hamdard, associated with HIMSR, New Delhi. URTI account for millions of visits to family physicians each year. Although warranted in some cases, antibiotics are greatly overused. In the present study, an overall antibiotic prescription rate for adult patients with URTI was 45.6% whereas 54.4% patients were on non-antibiotic treatment. In our study the antibiotics were prescribed in 10.5% cases of common cold, 76.47% cases of pharyngitis, 63.15% cases of laryngitis, 100% cases of otitis media and 52.38% cases of sinusitis. The most commonly prescribed antibiotic was azithromycin which was prescribed collectively in 70.3% cases of common cold, pharyngitis, laryngitis, and sinusitis. The combination of amoxicillin and clavulanic acid was prescribed in remaining 29.7% cases suffering from pharyngitis. sinusitis, and otitis media. The antibiotic prescription at Hospital is in line with the ICMR guidelines for URTIs. We found adverse drug reactions in only 9% cases receiving azithromycin and combination of amoxicillin and clavulanic acid. The adverse drug reaction reported with azithromycin was diarrhoea, stomach pain, nausea and vomiting whereas only diarrhoea was reported with amoxicillin and clavulanic acid combination. No other unexpected adverse drug reaction was observed in this study. Keywords: URTI, Antibiotics, Azithromycin and co-morbidities.